2008
DOI: 10.1002/ange.200800473
|View full text |Cite
|
Sign up to set email alerts
|

Sc3N@C80‐Ferrocene Electron‐Donor/Acceptor Conjugates as Promising Materials for Photovoltaic Applications

Abstract: Mit Potenzial für die Photovoltaik: Das erste Konstrukt, in dem ein endohedrales Trimetallnitridfulleren kovalent mit einer Donorgruppe verknüpft ist, wurde durch eine effiziente 1,3‐dipolare Cycloaddition erhalten. Dass das N‐Methyl‐2‐ferrocenyl‐Ih‐Sc3N@C80‐fulleropyrrolidin ausschließlich in Form des [5,6]‐Regioisomers isoliert wird, ließ sich NMR‐spektroskopisch und elektrochemisch nachweisen (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 24 publications
(12 reference statements)
2
50
0
2
Order By: Relevance
“…[20] This effect was attributed to a facile photoinduced electron transfer between the film and the EMF. In a ferrocene adduct of Sc 3 N@C 80 (I h ), recently reported by Echegoyen and co-workers, [21] photoinduced electron transfer between the ferrocene moiety and the fullerene was detected, and the radical ion pair obtained was significantly stabilized relative to a similar ferrocene-C 60 dyad. The application of metallofullerenes to the field of photovoltaics thus seems even more promising than that of the more conventional fullerenes.…”
Section: Emfs For Molecular Electronics and Photonicsmentioning
confidence: 86%
See 2 more Smart Citations
“…[20] This effect was attributed to a facile photoinduced electron transfer between the film and the EMF. In a ferrocene adduct of Sc 3 N@C 80 (I h ), recently reported by Echegoyen and co-workers, [21] photoinduced electron transfer between the ferrocene moiety and the fullerene was detected, and the radical ion pair obtained was significantly stabilized relative to a similar ferrocene-C 60 dyad. The application of metallofullerenes to the field of photovoltaics thus seems even more promising than that of the more conventional fullerenes.…”
Section: Emfs For Molecular Electronics and Photonicsmentioning
confidence: 86%
“…[21,65] The chosen electron donors were extended tetrathialfulvalene (exTTF) and ferrocene (Fc). The exTTF adduct of Y 3 N@C 80 was very unstable and was rapidly oxidized to an anthraquinone (AQ) adduct.…”
Section: Influence Of Exohedral Derivatizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very attractive Abstract: Bingel-Hirsch derivatives of the trimetallic nitride template endohedral metallofullerenes (TNT-EMFs) Sc 3 N@I h -C 80 and Lu 3 N@I h -C 80 were prepared by reacting these compounds with 2-bromodiethyl malonate, 2-bromo-1,3-dipyrrolidin-1-ylpropane-1,3-dionate bromide, and 9-bromo fluorene. The mono-adducts were isolated and their 1 H NMR spectra showed that the addition occurred with high regioselectivity at the [6,6] bonds of the I h -C 80 fullerene cage. Electrochemical analysis showed that the reductive electrochemistry behavior of these derivatives is irreversible at a scan rate of 100 mV s…”
Section: Introductionmentioning
confidence: 99%
“…Trimetallic nitride template endohedral metallofullerenes (TNT-EMFs) [1,2] have received the attention of many research groups, since they offer the possibility of encapsulating diverse metals inside fullerene cages to yield novel materials with potential applications in medicine, [3][4][5] organic solar cell device construction [6][7][8][9][10] and nanomaterials science. Exohedral functionalization is important for increasing the solubility and/or tuning the electronic properties of these fullerenes in order to expand the range of potential applications.…”
Section: Introductionmentioning
confidence: 99%